BIOFUELS: FIVE MYTHS OF THE AGRO-FUELS TRANSITION - Holt-Giménez, Eric (REVISTA NERA, 2012)
The goal of this article is to present the perverse nature of the discourse made by governments and trade companies about biofuels. These discourses consider them as an alternative totally efficient to replace petroleum an to solve the problem of green house gas emissions by burning petroleum derived fuels. In order to reach the objective proposed here, it is presented the contradictions of five myths related to biofuels: 1) Agro-fuels are clean and green; 2) Agro-fuels will not result in deforestation; 3) Agro-fuels will bring rural development; 4) Agro-fuels will not cause hunger; 5) Better “second-generation” agro-fuels are just around the corner.